A High Efficiency Chlorophyll Sensitized Solar Cell with Quasi Solid PVA Based Electrolyte - Hassan, H.C.; Abidin, Zul Hazrin Zainal; Chowdhury, F.I.; Arof, Abdul Kariem (Hindawi Publishing Corporation, 2016)
The objective of this work is to investigate the performance of chlorophyll sensitized solar cells (CSSCs) with gel electrolyte based on polyvinyl alcohol (PVA) with single iodide salt (potassium iodide (KI)) and double salt (KI and tetrapropylammonium iodide (TPAI)). Chlorophyll was extracted from the bryophyte Hyophila involuta. The CSSC with electrolyte containing only KI salt produced a short circuit current density () of 4.59 mA cm−2, open circuit voltage () of 0.61 V, fill factor (FF) of 0.64, and efficiency () of 1.77%. However, the CSSC with double salt electrolyte exhibited of 5.96 mA cm−2, of 0.58 V, fill factor FF of 0.58, and of 2.00%. Since CSSC with double salt electrolyte showed better efficiency, other cells fabricated will use the double salt electrolyte. On addition of 0.7 M tetrabutyl pyridine (TBP) to the double salt electrolyte, the cell’s efficiency increased to 2.17%,  mA cm−2,  V, and FF = 0.73. With 5 mM chenodeoxycholic acid (CDCA) added to the chlorophyll, the light to electricity efficiency increased to 2.62% with of 8.44 mA cm−2, of 0.54 V, and FF of 0.58.